A Rarely Seen Multilevel Thoracic Vertebral Fracture after a Nocturnal Hypoglycemic Convulsion Attack - Ebru Atalar; Cuneyd Gunay; Hakan Atalar; Tugba Tunc (Case Reports in Orthopedics)
A 49-year-old male presented with acute midthoracic severe back pain following a witnessed nocturnal convulsion attack. There was no history of trauma and the patient had a 23-year history of Type I diabetes mellitus. MRI scans of the thoracic spine revealed compression fractures at T5, T6, T7, and T8 vertebrae. The patient was treated conservatively. At 17 months after the initial diagnosis, the complaints of back pain had been resolved and the patient was able to easily undertake daily living activities. Hypoglycaemia is a common problem in diabetic patients treated with insulin. Convulsions may occur as a consequence of insulin-induced hypoglycemia. Nontraumatic compression fractures of the thoracic spine following seizures are a rare injury. Contractions of strong paraspinal muscles can lead to compression fracture of the midthoracic spine. Unrecognized hypoglycaemia should be considered to be a possible cause of convulsions in insulin-dependent diabetic patients. The aim of this report is to point out a case of rarely seen multilevel consecutive vertebrae fractures in a diabetic patient after a nocturnal hypoglycaemic convulsion attack.